2021
DOI: 10.1021/jacs.0c13458
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous and Highly Thermal Conductive Thin Film of Single-Crystal Covalent Organic Frameworks Ribbons

Abstract: Nanoporous materials are widely explored as efficient adsorbents for the storage of gases and liquids as well as for effective low-dielectric materials in large-scale integrated circuits. These applications require fast heat transfer, while most nanoporous substances are thermal insulators. Here, the oriented growth of micrometer-sized single-crystal covalent organic frameworks (COFs) ribbons with nanoporous structures at an air−water interface is presented. The obtained COFs ribbons are interconnected into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…The COF-366 films with different amounts of CNCs showed similar Raman spectra. In the films, the characteristic peaks at 1282 cm −1 and 1672 cm −1 of the two monomers disappeared, meanwhile, the C=N bond stretching vibration at 1593 cm −1 was generated [ 34 , 35 ]. The Raman spectra demonstrated the formation of imine bonds in the Schiff reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The COF-366 films with different amounts of CNCs showed similar Raman spectra. In the films, the characteristic peaks at 1282 cm −1 and 1672 cm −1 of the two monomers disappeared, meanwhile, the C=N bond stretching vibration at 1593 cm −1 was generated [ 34 , 35 ]. The Raman spectra demonstrated the formation of imine bonds in the Schiff reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently reported pure polymer films with high intrinsic k are presented in Table 2 . One can see that the most common molecular engineering strategies to enhance the intrinsic k of polymer includes the alignment of polymer chains through stretching, the increase of degree of crystallinity with heat treatment and the improvement in the molecules interactions [ 76 , 77 ]. Atomistic simulations and numerical predictions suggested that individual crystalline PE chain exhibits extraordinary high intrinsic k , over 237 W (mK) −1 [ 31 ].…”
Section: High-performance Thermally Conductive Filmsmentioning
confidence: 99%
“…[ 21 ] Some of the films, especially those gained at liquid‐containing interfaces could be readily transferred onto arbitrary substrates (including electrodes), which facilitated their integration in devices. These films have shown great promise in nanofiltration, [ 16,22 ] molecular separation, [ 18 ] photochemical sensing, [ 23 ] anion transport, [ 24 ] heat conduction, [ 25 ] and proton conduction. [ 26 ] Despite the wide development of freestanding thin films of 2D COFs, the synthesis of their 3D analogues and subsequent integration in devices remains challenging.…”
Section: Background and Originality Contentmentioning
confidence: 99%